Hybridization and Polyploidization of Saccharomyces cerevisiae Strains by Transformation-Associated Cell Fusion - Takagi, Atsuko (1985)
Hybrid or polyploid clones of Saccharomyces cerevisiae produced by protoplast fusion were easily isolated by selecting transformants with the plasmid phenotype because the transformation was directly associated with cell fusion. When haploid cells were used as the original strain, the transformants were mostly diploids with a significant fraction of polyploids (triploids or tetraploids). Repeated transformation after curing the plasmid gave rise to clones with higher ploidy, but the frequency of cell fusion was severely reduced as ploidy increased.